Kewajiban Suami Dalam Pemberian Nafkah Istri - Fahrezi, Irgi (Jurnal El-Thawalib, 2022)
Tablighi Jamaat is not an organization originating from Indonesia but a transnational organization originating from India. The founder of the Tablighi Jamaat is Muhammad Ilyas al-Kandahlawy, born in 1303 AH in the village of Kandalah in the Muzhafar Nagar region, North Banladesh India. He died on 11 Rajab 1363 H. His full name was Muhammad Ilyas bin Muhammad Isma'il Al-Hanafi Ad-Diyubandi Al-Jisyti Al-Kandahlawi then Ad-Dihlawi. Al-Kandahlawi is the origin of the word Kandalah, a village located in the Sahranfur area. While Ad-Dihlawi is another name for Dihli (New Delhi) the capital of India. It is in this country that the headquarters of the Tablighi Jamaat movement is located.This research is a field research (field research) and this research uses an analytical description approach. The data collection techniques in this study are interviews, observation, and documentation. The subjects of this study consisted of 3 families in Merangin Regency, Jambi Province as samples and Secondary Informants, namely the Tablighi Jamaat Community in Merangin Regency, Jambi Province.Based on research that the obligation to provide a living among the Tablighi Jamaat Community in Merangin Regency has been running according to what is in the Compilation of Islamic Law Article 80 Paragraph 4. Because every congregation who wants to go for khuruj they have to prepare a living that will be lived and needs during khuruj, they also have to ask permission in advance from the family who will be left behind.